Synergistic Control of Bacterial Fruit Blotch Using Bacillus velezensis ZY1 and Chemical Bactericides - Haoyu Wei; Sheng Han; Maihemuti Mijiti; Tingchang Zhao; Wei Guan; Yuwen Yang (Agronomy)
Bacterial fruit blotch (BFB) is a devastating disease caused by Acidovorax citrulli, severely impacting the watermelon and melon industries and leading to significant economic losses. Currently, researchers have not identified any commercial melon varieties with high resistance to BFB, and farmers primarily rely on chemical agents for prevention and control. However, the extensive use of these agents contributes to increased drug resistance among pathogenic bacteria, making it essential to develop environmentally friendly control methods. To explore the feasibility of combining the Bacillus velezensis ZY1 strain with chemical agents for BFB management, we assessed the efficacy of 10 bactericides and the ZY1 strain against Acidovorax citrulli. The results show that Prothioconazole, Zhongsheng Tetramycin Solution, Streptomycin Sesquisulfate, Tetramycin, Zhongshengmycin, and ZY1 exhibited significant inhibitory effects on the growth of Acidovorax citrulli. We determined the biocompatibility of the bactericides with the ZY1 strain using the plate confrontation method and the flat counting method. Zhongsheng Tetramycin Solution, Zhongshengmycin, and Kasugamycin exhibited good compatibility with the ZY1 strain. Additionally, we established the optimal compounding ratio of the bactericide and ZY1 using the Horsfall method. Among these, Zhongshengmycin demonstrated the best performance when combining its efficacy against Acidovorax citrulli with its biocompatibility with the ZY1 strain. The combination of Zhongshengmycin and ZY1 at a volume ratio of 5:5 significantly inhibited Acidovorax citrulli, exhibiting a clear synergistic effect with a synergy index (IR) value of 1.542. Field tests conducted over 21 days in Beijing greenhouses, Hainan Field facility greenhouses, and Xinjiang showed that the control efficacy of the Zhongshengmycin and ZY1 combination (89.23%) significantly surpassed that of the single agent Zhongshengmycin (80.35%) and the biocontrol bacterium ZY1 (72.12%). Notably, the application rate of Zhongshengmycin in the mixture was only half that of the single agent, resulting in a significant reduction in chemical usage. The combination of Bacillus velezensis ZY1 and Zhongshengmycin not only decreases chemical usage but also significantly enhances control efficacy compared to using Zhongshengmycin alone.